PENYULUHAN TENTANG PENGGUNAAN RAMUAN HERBAL PADA IBU HAMIL DI KECAMATAN MANE KABUPATEN PIDIE - Yuliana, Yuliana; Idawati, Idawati; Warni, Eka (Jurnal Adiguna Pengabdian Masyarakat, 2024)
The prevalence of herbal medicine use is increasing worldwide, especially among pregnant women. In the Pidie area, it is still very thick with the culture and belief in the use of herbs that are concocted by themselves for maternal health both before pregnancy and even during pregnancy. Published literature shows the prevalence of herbal medicine use varies between 22.3-82.3% during pregnancy. The most commonly used herbs are peppermint, ginger, thyme, chamomile, sage, anise, fenugreek, and green tea. The most common reason for its intended use is for the treatment of gastrointestinal disorders and cold and flu symptoms. The majority of use during the first trimester of pregnancy is without consultation with a doctor or midwife. The majority of pregnant women are recommended by families because it is more effective and has fewer side effects than modern treatments, especially during pregnancy. Many pregnant women do not know the risks of using herbal herbs for their pregnancy, so this community service activity needs to be carried out in order to provide knowledge for pregnant women about the use of herbs during pregnancy. The method that will be used in this community service activity is counseling involving pregnant women, women of childbearing age, families and village officials. The results obtained from this counseling enthusiastic pregnant women participated in the activity and were active in asking questions, showing that the information conveyed by the presenter increased the understanding and knowledge of pregnant women about the use of herbal herbs which has been a tradition that has been valid in the family and community